A Green Approach to Surface Modification of Cellulose Nanocrystals via Grafting of Poly(2-hydroxyethyl methacrylate) and Development of Polybutylene-Adipate-Terephthalate-Based Nanocomposites - Yilmaz Arikan, Eda Jan; Alkan Goksu, Yonca; Altinbay, Aylin; Vatansever, Emre; Acar, Sezer Enes; Bidis, Yusuf Ziya; Nofar, Mohammadreza (MDPI, 2026)
Cellulose nanocrystals (CNCs) possess outstanding mechanical properties and sustainability; however, their hydrophilic nature makes their dispersion challenging in hydrophobic bioplastic matrices. Surface modification of CNC is therefore inevitable for effective nanocomposite fabrication. In this study, CNC surface was modified using a green, water-based grafting-from method, enabling the growth of poly(2-hydroxyethyl methacrylate) (PHEMA) chains directly from its surface. This modification decreases intermolecular hydrogen bonding among CNCs and enhances their compatibility with poly(butylene adipate-co-terephthalate) (PBAT), a commercially available biodegradable aliphatic-aromatic copolyester widely used in sustainable packaging applications. The enhanced interfacial interaction arises from both the improved dispersion of CNCs within the PBAT matrix and the ability of PHEMA's hydroxyl groups to form secondary interactions with PBAT. To examine how grafted polymer chain length influences CNC dispersion, PHEMA was grown from CNC surfaces at different grafting degrees. Additionally, PHEMA homopolymers were synthesized and melt-mixed with PBAT to evaluate the role of PHEMA in the absence of CNC. Neat and modified CNCs (mCNCs) were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, water contact angle measurements, wettability tests, and thermogravimetric analysis. Nanocomposites containing 3 wt% neat CNCs, mCNCs, or PHEMA homopolymers were subsequently prepared using an internal melt mixer. Melt rheology, differential scanning calorimetry, and dynamic mechanical analysis were then used to characterize the final viscoelastic and thermomechanical behavior of the resulting nanocomposites. The increased storage modulus and complex viscosity of the nanocomposites confirmed that the CNCs grafted with an intermediate PHEMA chain length exhibited improved network formation and enhanced interfacial interaction with PBAT.
Keywords: cellulose nanocrystals; surface modification; PHEMA; PBAT; rheology; POLYMER NANOCOMPOSITES; NANOCELLULOSE; CNC; REINFORCEMENT; POLYLACTIDE; DISPERSION; BEHAVIOR; Materials Science